The Role of Religious Leaders in Instilling Islamic Moderation During the Covid-19 Pandemic: Megawati, Muhiddin Bakri, Iskandar - Megawati; Muhiddin Bakri; Iskandar (IAIN Parepare, 2022)
Islamic moderation must be understood as a balance related to respect for people who have different understandings, harmony and tolerance are created because of a sense of moderation. One of the creations or realization of peace is because it is able to maintain balance and tolerance. in minimizing the problems of Islamic moderation in the midst of the COVID-19 pandemic.This study uses a qualitative descriptive approach with data collection techniques of observation, interviews and documentation. Information consists of several religious leaders in Watang Pulu Village, Pinrang Regency. The results of the study indicate that religious leaders are figures who can be imitated and guide the community. In this case, the role played by religious leaders in instilling Islamic moderation in Watang Bulu Village is by instilling a positive attitude towards the community regarding differences and views or opinions of the community regarding differences or opinions. the community about how to worship in the midst of the covid-19 pandemic. From the results of the study that the strategy carried out by religious leaders in minimizing the problems of Islamic moderation in Watang Pulu Village was to open the role of dialogue, socialization, routine studies and social activities, religion, of course, while still paying attention to health protocols in the midst of the covid-19 pandemic.